Kaomu, Papara dan Walaka : Satu Kajian mengenai Struktur Sosial dan Ideologi Kekuasaan di Kesultanan Wolio - Tony Rudyansjah (Antropologi Indonesia, 1997)
This article attempts to explain the basic nature of social structure of the Sultanate of Wolio which is divided into four categories, namely Kaomu, Walaka, Papara and Batua. The analysis itself is based on local manuscripts and fieldwork in the Sultanate of Wolio in the course of several years. Through the study of Wolio social structure, the writer also attempts to comprehend the ideology of power in Wolio society. In addition, the discussion shows as well the misinterpretation of the basic nature of Wolio social structure and ideology of power done by several Dutch scholars since 1878.